SWOT Analysis of The Wulan Coffee Agroindustry Based on Geographic Indications - Novita, Elida; Savira, Ultania Yisca; Purnomo, Bambang Herry; Pramitasari, Noven; Wahono, Puji; Pradana, Hendra Andiananta; Ismaniar Rahmadaningtyas, Resta Dwi (agriTECH, 2024)
Wulan Coffee Agroindustry is among the coffee-producing centers in Maesan Sub-district, Tanah Wulan Village. This Sub-district is included in the area to apply for certification by the Geographical Indication Protection Society (GIPS) for Hyang Argopuro Arabica Coffee products. Therefore, this research aimed to formulate a strategic recommendation for developing the Wulan Coffee Agroindustry in dealing with GI certification using the SWOT method. The study included identifying internal and external factors, weighting, and strategy analysis using the SWOT method. The results showed that the total score of the IFAS matrix was 1.178 while the EFAS matrix was 0.070, indicating the IE matrix’s position was in the first quadrant of the aggressive strategy. In quadrant I, an aggressive strategy could maximize the strength possessed by Wulan Coffee Agroindustry to deal with existing threats. The aggressive strategy consisted of implementing and maintaining SOP related to sustainable coffee cultivation and production methods, increasing promotional efforts, and branding of monthly coffee products based on GI. This strategy also included certification efforts for export product development, and improvement of coffee agrotourism clusters comprising several stakeholders such as village, sub-district, and the local government of Bondowoso Regency.